Implementasi Pasal 65 Ayat 1 Undang-Undang No. 32 Tahun 2009 Terhadap Masyarakat yang Terkena Dampak Pengusahaan Pertambangan Pasir - Muhammad Panji Mahardika; Dewi Astutty Mochtar; Diah Aju Wisnuwardhani (MLJ Merdeka Law Journal, 2020)
This study aims to find out how the implementation of article 65 paragraph 1 of Law No.32 of 2009 and the legal protection of people affected by sand removal in Lumajang Regency. Based on the law adjusted to the experience that occurs in the community to better know and understand the law as a set of rules or positive norms that apply. That the Lumajang District community has a legal protection. But unfortunately, this regulation is not used as a reference for the government in managing the resources contained in Lumajang regency in the form of sand mining assets. In general, the existence of mining will result in losses both in the environment and for the people who live around the mining area. In this case the rights of the Lumajang district community have been violated, such as the right to a healthy life, the right to safety and comfort, and the right to prosperity.DOI: https://doi.org/10.26905/mlj.v1i1.4290.